A contribution to the Slovenian spider fauna – II - Rok Kostanjšek; Alenka Gorjan (Natura Sloveniae)
The present study reports on and discusses new records for the Slovenian spider fauna, namely: Asthenargus bracianus, Clubiona leucaspis, Euryopis laeta, Lasaeola prona, Lathys stigmatisata, Meioneta innotabilis, Oecobius maculatus, Porrhomma microphthalmum, Trichoncus saxicola and Zodarion pusio. According to their areas of distribution and confirmed presence in the neighbouring countries, the presence of newly recorded species in Slovenia can be considered as expected, indicating still incomplete knowledge of Slovenian spider fauna.